Influência da temperatura sobre a translocação axial de fotoassimilados e na formação de lesões no caule de cafeeiros (Coffea arabica L.) - Silva, J E; Sant'Anna, R; Ferreira, L G R (Revista Ceres, 2025)
The effect of temperature on the axial translocation of photoassimilates and on the induction of stem lesions was studied in young coffee plants (Coffea arabica L.). The one-hour temperature treatments were localized in the stem region near the soil surface, varying from -5 to 50°C. After the treatments, 14COg was supplied to one mature leaf of each plant under conditions of 4,000 lux of light intensity and room temperature. The radioactivity of the plant parts was measured by liquid scintillation counting. Treatments using temperature extremes were also done to detect morphological alterations in the stem. Although the results may suggest a relationship between the amount of 14C assimilated and temperature, it is thought that the observed variations were mainly due to differences in leaf areas and gas chamber volumes. The amount of radioactivity exported by the treated leaves was independent of the stem temperature and of the rate of 14COg assimilation. The temperature of treatment greatly affected the distribution of the radioactivity among the different plant parts. A 14C accumulation was quite pronounced in the roots between 15 and 30°C, indicating a predominance of the descending flow of photoassimilates. Below 15°C and above 35°C, the 14C levels were rather small in the roots, while much higher amounts were found in the parts above the treated region. This shows that translocation through the treated segment of the stem was inhibited. Under temperature extremes, stem lesions appeared in the treated region. When the damage of the tissues was high, the plants did not recover and died.